Potential Impact and Cost-Effectiveness of Condomless-Sex–Concentrated PrEP in KwaZulu-Natal Accounting for Drug Resistance. (18th December 2019) - Phillips, Andrew N; Cambiano, Valentina; Johnson, Leigh; Nakagawa, Fumiyo; Homan, Rick; Meyer-Rath, Gesine; Rehle, Thomas; Tanser, Frank; Moyo, Sizulu; Shahmanesh, Maryam; Castor, Delivette; Russell, Elizabeth; et al.
Abstract: Introduction: Oral preexposure prophylaxis (PrEP) in the form of tenofovir-disoproxil-fumarate/emtricitabine is being implemented in selected sites in South Africa. Addressing outstanding questions on PrEP cost-effectiveness can inform further implementation. Methods: We calibrated an individual-based model to KwaZulu-Natal to predict the impact and cost-effectiveness of PrEP, with use concentrated in periods of condomless sex, accounting for effects on drug resistance. We consider (1) PrEP availability for adolescent girls and young women aged 15–24 years and female sex workers, and (2) availability for everyone aged 15–64 years. Our primary analysis represents a level of PrEP use hypothesized to be attainable by future PrEP programs. Results: In the context of PrEP use in adults aged 15–64 years, there was a predicted 33% reduction in incidence and 36% reduction in women aged 15–24 years. PrEP was cost-effective, including in a range of sensitivity analyses, although with substantially reduced (cost) effectiveness under a policy of ART initiation with efavirenz- rather than dolutegravir-based regimens due to PrEP undermining ART effectiveness by increasing HIV drug resistance. Conclusions: PrEP use concentrated during time periods of condomless sex has the potential to substantively impact HIV incidence and be cost-effective. Abstract : PrEP use concentrated during time periods of condomless sex has the potential to substantively impact HIV incidence and to be cost-effective in the example setting of KwaZulu-Natal, South Africa.